2016
DOI: 10.1016/j.physa.2016.06.090
|View full text |Cite
|
Sign up to set email alerts
|

Do foreign exchange and equity markets co-move in Latin American region? Detrended cross-correlation approach

Abstract: This paper investigates the dynamics of the relationship between foreign exchange markets and stock markets through time varying co-movements. In this sense, we analyzed the time series monthly of Latin American countries for the period from 1991 to 2015. Furthermore, we apply Granger causality to verify the direction of causality between foreign exchange and stock market and detrended cross-correlation approach (DCCA ) for any co-movements at different time scales. Our empirical results suggest a positive cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 34 publications
4
17
0
Order By: Relevance
“…The first one is a bidirectional causality between market capitalization (CAP) and foreign exchange market (EX). This fact confirms the results of Pan et al (2007), Malarvizhi and Jaya (2012), Kumar (2013), Caporale et al (2014), Do et al (2015) and Bashir et al (2016). Malarvizhi and Jaya (2012) find that there is Bashir et al (2016) a bidirectional causal relationship between the exchange rate and the Nifty; i.e.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The first one is a bidirectional causality between market capitalization (CAP) and foreign exchange market (EX). This fact confirms the results of Pan et al (2007), Malarvizhi and Jaya (2012), Kumar (2013), Caporale et al (2014), Do et al (2015) and Bashir et al (2016). Malarvizhi and Jaya (2012) find that there is Bashir et al (2016) a bidirectional causal relationship between the exchange rate and the Nifty; i.e.…”
Section: Resultssupporting
confidence: 80%
“…This fact confirms the results of Pan et al (2007), Malarvizhi and Jaya (2012), Kumar (2013), Caporale et al (2014), Do et al (2015) and Bashir et al (2016). Malarvizhi and Jaya (2012) find that there is Bashir et al (2016) a bidirectional causal relationship between the exchange rate and the Nifty; i.e. changes in stock market affect the exchange rate.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These effects mean that the negative crisis effects spill over more quickly and with more severe consequences compared to the normal times. Furthermore, the dot-com crisis was also characterized by such effects [109], as was the global financial crisis [110] and the Eurozone debt crisis as well [111]. The negative effects of the COVID-19 crisis compared to the aforementioned ones was confirmed in [112], where authors found similar characteristics regarding stock markets' reactions to those of previous crises.…”
Section: Discussionmentioning
confidence: 89%
“…This method, which consists of a generalisation of the detrended fluctuation analysis (DFA) proposed by Peng et al (1994) to detect temporal dependence in time series, has the advantage of being applied in the context of nonstationarity (see, e.g., Zebende et al, 2013;Kristoufek, 2014), thereby circumventing econometric problems related to unit roots and periodic trends that may lead to spurious results. As documented by Bashir et al (2016), the DCCA correlation coefficient proposed by Zebende (2011) proved to be more robust than the linear models in the presence of such issues. Accordingly, by means of this methodology it is possible to grasp if there are co-movements between equity and debt instruments at different scales, which may be relevant to support investors' decisions.…”
Section: Introductionmentioning
confidence: 91%